Applying the impairment, activity limitation, and participation restriction constructs of the ICF model to osteoarthritis and low back pain trials: a reanalysis. - Ayis, S; Arden, N; Doherty, M; Pollard, B; Johnston, M; Dieppe, P (2010)
OBJECTIVE: To test the hypothesis that interventions targeting the relief of pain and disability in musculoskeletal diseases may have differential effects on activity limitation and participation restriction as defined in the International Classification of Functioning, Disability and Health (ICF). METHODS: Full data were obtained for 3 randomized controlled trials that used the Western Ontario and McMaster Universities Osteoarthritis Measure (WOMAC), the Medical Outcomes Study Short-form 36 (SF-36), or the Oswestry Disability Questionnaire as their primary outcome measures. The trial outcomes were reanalyzed using items previously designated as assessing pure activity limitation (A) or participation restriction (P), or a mixture of the 2 (A/P) only, and the results compared with the outcomes found using the full scales, which assess a mixture of outcome domains. RESULTS: The results did not refute the hypothesis. An exercise-based intervention and injection therapies both appeared to have more effect on participation restriction (P) than on activity limitation (A), while a drug-based intervention had more effect on A than on P. CONCLUSION: Different interventions used to treat musculoskeletal disorders may have differential effects on impairment, activity limitation, and restricted participation. The use of outcome measures that do not differentiate these 3 domains may obscure the true value of an intervention.